Does Axillary Reverse Mapping Prevent Lymphedema After Lymphadenectomy?. Issue 5 (May 2017) - Tummel, Evan; Ochoa, Daniela; Korourian, Soheila; Betzold, Richard; Adkins, Laura; McCarthy, Maureen; Hung, Stephanie; Kalkwarf, Kyle; Gallagher, Kristalyn; Lee, Jeannette Y.; Klimberg, V. Suzanne
Abstract : Background: We hypothesized that disconcerting lymphedema rates in both sentinel lymph node biopsy (SLNB) and axillary lymph node dissection (ALND) may be because of unrecognized vunerable variations in arm lymphatic drainage within the axilla. Axillary reverse mapping (ARM) facilitates identification and avoidance of arm lymphatics within the axilla and its use may reduce lymphedema. Methods: This institutional review board-approved study from June 2007 to December 2013 involved patients undergoing SLNB with or without ALND, or ALND alone. Technetium is injected subareolarly for localization of the breast SLN and isosulfan blue dye (5 mL) is injected in the ipsilateral upper arm for localization of nonbreast lymphatics. Data were collected on identification and preservation of arm lymphatics, crossover rates, blue node metastases, axillary recurrence, and lymphedema as measured by volume displacement. Results: A total of 654 patients prospectively underwent 685 ARM procedures with a SLNB and/or ALND. Objective lymphedema rates for SLNB and ALND were 0.8% and 6.5% respectively, with 26-month median follow up. Blue lymphatics were identified in 29.2% (138/472) of SLNB and 71.8% (153/213) of ALND. Crossover was seen in 3.8% (18/472) of SLNB and 5.6% (12/213) of ALND. Blue node metastases rate was 4.5% (2/44). Axillary recurrence rate was 0.2% and 1.4% for SLNB and ALND, respectively. Conclusions: ARM allows frequent identification of arm lymphatics in the axilla, which would have been transected during routine surgery. Rates of metastases in noncrossover nodes and axillary recurrences are low. Lymphedema rates are dramatically reduced using ARM when compared with accepted standards.